KETERLIBATAN ORANG TUA DALAM MENDUKUNG PENDIDIKAN AGAMA ISLAM TERHADAP PERKEMBANGAN AKHLAK - Ach Kholil (UNISAN JURNAL, 2024)
Parental guidance plays a crucial role in a child's development, encompassing the nurturing of their talents, interests, and abilities, fostering self-awareness, and equipping them with problem-solving skills to navigate life responsibly and independently. This study investigates parental guidance in fostering Akhlak and spiritual development in children. Findings reveal various parental approaches to guidance: while some parents are actively engaged in tutoring their children, others exhibit apathy due to household responsibilities. However, those who provide guidance prioritize their children's Akhlak and spiritual development, albeit with some areas for improvement. Supportive factors include parental awareness and commitment to educating and guiding their children, fostering a nurturing family environment conducive to learning. Conversely, factors hindering guidance efforts include technological distractions like smartphones and television, which disrupt children's learning activities, as well as peer influence leading to a preference for play over learning Moreover, notable differences emerge between children receiving parental guidance and those without it, particularly in their adherence to school rules and overall Akhlak development. Children under parental guidance tend to display greater obedience and adherence to school regulations compared to their peers without such guidance. In summary, parental guidance significantly impacts children's Akhlak development, with engaged parents fostering a conducive learning environment and guiding their children towards responsible behavior, despite challenges posed by modern distractions and external influences.